The Function Of Information And Communication Technology In The Teaching And Learning Process During The COVID-19 Pandemic - Siahaan, Chontina; Natonis , Aprianer (CV. Inara, 2022)
This paper is intended to provide permanent information about learning in the era of the Covid-19 pandemic in utilizing information and communication technology. Based on the fact that most educators are not very familiar with managing information technology and communication and not all educational institutions feel the existence of technology that can support teaching and learning activities so that in the era of the Covid19 pandemic, there are still many schools that do the learning process manually, namely by providing modules or tasks to students to be done at home. This study was conducted using framing analysis of the phenomenon faced by teachers, especially teachers in Indonesia in an effort to improve competence in the era of the Covid-19 pandemic. The use of technology in the learning process can trigger increased interest and motivation for learning students until the quality of their learning increases. The use of gadgets that are commonly used by students in the present era in the teaching and learning process is expected to improve the quality of the teaching and learning process itself.